HALF-FACTORIALITY IN SUBRINGS OF TRIGONOMETRIC POLYNOMIAL RINGS - ullah, ehsan (Trends in Computational and Applied Mathematics, 2013)
In this study we explore half-factorial domains in trigonometric polynomial rings. Consider the ring T^′ of complex trigonometric polynomials. (see PP). We construct the half-factorial domains T_2^′ , % T_3^′ and T_4^′ which are the subrings of T^′ such that T_2^′ T_3^′ T_4^′ T^′ . We also discuss among these subrings the Condition: Let AB be a unitary (commutative) ring extension. For each % xB there exist x^′ U(B) and x^′ ′ A such that x=x^′ x^′ ′ .